Cuidamos nuestro medio ambiente para vivir sanos - Galvez Espinoza, Elizabeth (2019)
My work has the purpose in education, that the students become aware of their food and the care of the environment, since in it there is every way of life._x000D_ The environment that includes the landscape, flora, fauna, air and the rest of the biotic and abiotic factors that characterize a certain place is known as the environment or natural environment._x000D_ Environmental education, therefore, is training oriented to the teaching of the functioning of natural environments so that human beings can adapt to them without harming nature. People must learn to lead a sustainable life that reduces the human impact on the environment and allows the subsistence of the planet._x000D_ My learning session was focused on students understanding the message of reading and then putting it into practice avoiding eating unfit meals for their health._x000D_ The reading told us about health care and non-communicable diseases, so we can avoid all kinds of illness.